2021
DOI: 10.1080/09537104.2021.1882668
|View full text |Cite
|
Sign up to set email alerts
|

Targeting platelet inhibition receptors for novel therapies: PECAM-1 and G6b-B

Abstract: While current oral antiplatelet therapies benefit many patients, they deregulate the hemostatic balance leaving patients at risk of systemic side-effects such as hemorrhage. Dual antiplatelet treatment is the standard approach, combining aspirin with P2Y 12 blockers. These therapies mainly target autocrine activation mechanisms (TxA 2 , ADP) and, more recently, the use of thrombin or thrombin receptor antagonists have been added to the available approaches. Recent efforts to develop new classes of anti-platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Indeed, PECAM1 has recently been identified as a potential novel target for antiplatelet therapy. 55 Interestingly, PECAM1-knockout mice also show reduced trabecular bone volume, an increased number of osteoclasts and enhanced bone resorption 56 while PT-VWD mice show enhanced trabecular bone volume, a decreased number of osteoclasts and decreased bone resorption, findings so far unexplained and possibly related to the role of PECAM1 as a negative regulator of osteoclastogenesis. 12 When we assessed the activation of Lyn substrates, namely Akt and Syk, we found decreased Akt phosphorylation after stimulation with ADP and convulxin in PT-VWD platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PECAM1 has recently been identified as a potential novel target for antiplatelet therapy. 55 Interestingly, PECAM1-knockout mice also show reduced trabecular bone volume, an increased number of osteoclasts and enhanced bone resorption 56 while PT-VWD mice show enhanced trabecular bone volume, a decreased number of osteoclasts and decreased bone resorption, findings so far unexplained and possibly related to the role of PECAM1 as a negative regulator of osteoclastogenesis. 12 When we assessed the activation of Lyn substrates, namely Akt and Syk, we found decreased Akt phosphorylation after stimulation with ADP and convulxin in PT-VWD platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting primary platelet activation pathways is also one of the recent efforts to develop new classes of antiplatelet drugs. Targeting the immunoreceptor tyrosine-based activation motif (ITAM)-containing collagen receptor GPVI/FcRγ-chain complex would provide platelet inhibition due to the role of these receptors in the downregulation of platelet ITAM-receptor signaling ( 94 ). The results from targeting GPVI are encouraging with reduced aggregation and smaller arterial thrombi, with no major bleeding complications.…”
Section: Therapeutic Targeting Of Platelet Subpopulationsmentioning
confidence: 99%
“…It has been suggested in the literature that both PECAM-1 (which inhibit signaling downstream of the collagen receptor GPVI and other platelet activation pathways, such as those mediated by ADP and thrombin), and G6b-B (which inhibits platelet activation by the ITAM-bearing receptors GPVI and CLEC-2) are worthy of consideration as targets for new antiplatelet therapy. For greater details on targeting PECAM-1 and G6b-B as antithrombotic targets, readers may refer to ( 94 ).…”
Section: Therapeutic Targeting Of Platelet Subpopulationsmentioning
confidence: 99%
“…Platelet endothelial cell adhesion molecule 1 (PECAM-1) is a transmembrane glycoprotein that belongs to the immunoglobulin superfamily. It is present on the surface of platelets, endothelial cells, monocytes, neutrophils, and lymphocytes [1]. Previous animal studies have shown that PECAM-1 plays an important role in the regulation of the thrombotic process and that increased expression and activity of this protein results in the inhibition of thrombus formation [2].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these motifs, Shp1 is located adjacent to phosphorylated ITAM and enables ITAM dephosphorylation, which inhibits the signaling pathway associated with platelet activation. The phosphorylation of ITIMs occurs after platelet activation or the clustering of PECAM-1 on the platelet surface [1]. PECAM-1 has also been shown to suppress ADP-and thrombin-induced platelet activation, but the precise molecular mechanism underlying this process is unknown [2].…”
Section: Introductionmentioning
confidence: 99%